Microbiota profile in sinonasal mucosa of chronic rhinosinusitis as an indicator for therapeutic outcome - Imam Megantara; Muhammad Fadhil Ihsan Yazid; Gita Widya Pradini; Melati Sudiro; Chrysanti Murad (Oto Rhino Laryngologica Indonesiana, 2021)
ABSTRACTBackground: Chronic rhinosinusitis (CRS) is characterized by persistent inflammation of the sinonasal mucosa, which often requires surgical and additional post-operative therapy. Microbial dysbiosis due to the imbalance of commensal bacteria and pathogens plays a crucial role in the inflammatory process within the sinonasal mucosa and in therapy outcome. Further knowledge about the microbiota profile in CRS is needed to improve the management strategy for CRS patients. Purpose: To review recent studies on the microbiota profile in sinonasal mucosa of CRS patients, and its potential as an indicator for therapeutic outcome. Literature review: Recent data from several studies has documented increased microbiota richness and diversity in post-operative CRS patients’ sinonasal mucosa, as well as good post-operative outcomes. Increased genus Corynebacterium abundance was also consistently associated with good post-operative outcomes. Conclusion: There was a difference in microbiota profiles in pre and post-operative CRS patients, indicating an association with clinical improvement. Corynebacterium was associated with better post-operative outcomes. Thus, the presence of these bacteria potentially could be used as an indicator for therapeutic outcome.Keywords: chronic rhinosinusitis, microbiota, endoscopic sinus surgery, therapeutic outcomeABSTRAKLatar belakang: Rinosinusitis kronis (RSK) merupakan kondisi inflamasi yang menetap pada mukosa sinonasal dan sering memerlukan operasi dan terapi tambahan pasca-operasi. Kondisi disbiosis mikrobiota akibat ketidakseimbangan bakteri komensal dan patogen diduga memengaruhi proses inflamasi pada mukosa sinonasal dan luaran terapi. Diperlukan pengetahuan tentang profil mikrobiota pada RSK sehingga diharapkan dapat meningkatkan strategi penanganan pasien RSK. Tujuan: Mempelajari studi terkini tentang profil mikrobiota pada mukosa sinonasal pasien RSK, dan potensinya sebagai indikator luaran terapi. Tinjauan pustaka: Data terkini dari beberapa penelitian menemukan peningkatan kekayaan dan keragaman mikrobiota pada mukosa sinonasal pasien RSK pasca-operasi dan memiliki hubungan dengan luaran operasi yang baik. Peningkatan kelimpahan genus Corynebacterium ditemukan secara konsisten berkaitan dengan luaran operasi yang baik. Kesimpulan: Terdapat perbedaan profil mikrobiota pada pasien RSK pra dan pasca-operasi yang mengindikasikan kaitannya dengan perbaikan klinis. Corynebacterium adalah bakteri yang ditemukan memiliki hubungan dengan luaran operasi yang lebih baik, sehingga keberadaan bakteri ini berpotensi untuk dapat dimanfaatkan sebagai indikator luaran terapi.Kata kunci: rinosinusitis kronis, mikrobiota, operasi sinus endoskopik, luaran terapi